Adobe Photoshop, Illustrator, and InDesign collaboration and workflow - Wiele, Bart van de (Classroom in a book., 2022)
Even if you're already comfortable with Photoshop, Illustrator, or InDesign, Adobe Creative Cloud now offers powerful opportunities for improving efficiency and collaboration that few design and marketing professionals are using. In this hands-on, full-color tutorial, Adobe Solutions Consultant Manager Bart Van de Wiele helps you master these innovations—dramatically improving both team and individual efficiency in every print, web, video, UX, or online marketing project. Van de Wiele helps you establish powerful workflows that leverage the remarkable capabilities of Adobe's native file formats, and improve content collaboration via Adobe cloud documents and Creative Cloud Libraries. You'll find concise, focused insights for managing tradeoffs, so you can optimize workflows and collaboration strategies in your own organization. Packed with hands-on exercises built around realistic use cases, there's no better way to experience all the added value built into today's Adobe Creative Cloud—and discover all you can achieve by taking full advantage of Adobe's unparalleled integration and cloud resources.